rTMS and TENS Relieve Neuropathic Pain in CCI Model Rats by Modulating Central Nervous System TRPV1 and Neuroinflammation - Zhangyu Xu; Quanzhen Zhong; Fei Xing; Yuanliang Zhu; Yue Hu; Maomao Huang; Mouwang Zhou; Jianxiong Wang (Mediators of Inflammation)
Conclusion: Both rTMS and TENS effectively ameliorated CCI-induced NP, with rTMS of the PFC showing superior performance. Both treatments reduced TRPV1 expression and suppressed neuroinflammation in the spinal cord, indicating that this may be one of the mechanisms through which they exert their therapeutic effects.